(untitled) (Journal of Educational Sciences, 2022)
The article focuses on effective methods of developing students’ ethnocultural competence in higher education through the comparative study of Abai’s works translated into English with the authentic. The research aims to identify methods for the effective development of ethnocultural competence, based on the study of foreign language translations in comparison with the original. The major factor in the development of ethnocultural competence of university students as a theoretical significance is the justification of the content, methods and pedagogical conditions by substantiating the use of Abai’s translated poems as a tool of national culture. Ethnocultural competence combines the ability and readiness to act harmoniously on the basis of experience, accumulated in specially organized forms of education and upbringing in the course of life relations. For the development of ethnocultural competence through a comparative study of translations, the intercultural method, the contrast method, the method of exercises and open tasks, the method of conversation, discussion, and finally, to summarize the topics covered the cinquain method were used. The value of the research is the selection of effective methods of interaction in the development of ethnocultural competence of university students, studying Abai’s translations. The practical significance of the work lies in the factof offering a system of methods for the development of ethnocultural competence of university teachers and future professionals. Key words: Abay’s translations, ethnocultural competence, authentic, development, teaching methods.